Impact Response of Hammerhead Pier Fibrous Concrete Beams Designed with Topology Optimization - Salaimanimagudam, Meivazhisalai Parasuraman; Suribabu, Covaty Ravi; Murali, Gunasekaran; Abid, Sallal R. (Periodica Polytechnica Civil Engineering, 2020)
Reducing the weight of concrete beams is a primary (beyond strength and durability) concern of engineers. Therefore, this research was directed to investigate the impact response of hammerhead pier concrete beams designed with density-based method topology optimization. The finite element topology optimization was conducted using Autodesk fusion 360 considering three different mesh sizes of 7 mm, 10 mm, and adaptive meshing. Three optimized hammerhead beam configurations; HB1, HB2, and HB3, respectively, with volume reductions greater than 50 %. In the experimental part of this research, nine beams were cast with identical size and configuration to the optimized beams. Three beams, identical to the optimized beams, were tested under static bending for verification purposes. In comparison, six more beams, as in the preceding three beams but without and with hooked end steel fibers, were tested under repeated impact load. The test results revealed that the highest flexural capacity and impact resistance at crack initiation and failure were recorded for the adaptive mesh beams (HB3 and HB3SF). The failure impact energy and ductility ratio of the beam HB3SF was higher than the beams HB1SF and HB2SF by more than 270 %. The results showed that the inclusion of steel fiber duplicated the optimized beam’s impact strength and ductility several times. The failure impact resistance of fibrous beams was higher than their corresponding plain beams by approximately 2300 to4460 %, while their impact ductility ratios were higher by 6.0 to 18.1 times.